Fossil Fuel Alternatives: Renewable Energy and Nuclear: Energy - Amita Sari, Putu Ayu; Purwantoro, Susilo Adi; Firman Z., Yanda Dwira (International journal of technology and education research, 2025)
The use of fossil fuels (oil, gas, and coal) is still the mainstay of world energy for various reasons of its convenience. Although currently fossil fuels are also accused of being the main cause of climate change and global warming, it is not that easy to replace them with clean energy. There is still a transition period between dependence on fossil energy so that it can later be changed into green energy. Renewable energy is indeed planned to be the main energy source in the future because it will not run out. However, its management still experiences various obstacles such as costs or distribution. Some examples of renewable energy, for example solar, wind, bioenergy, tides, geothermal, water, nuclear, and others can be fully utilized for energy by changing its form to produce electricity or heat. Nuclear is also included in Indonesia's plan to start developing reactors so that they can be used commercially in the future. In the energy transition plan with its various obstacles, a combination of fossil fuels alongside renewable energy is used, which is called a hybrid system. This syst em can consist entirely of renewable energy or a combination of two or more fossil fuels and renewable energy. In addition to its better effectiveness, greenhouse gas emissions can also be reduced with this mechanism. That is why it is also important to develop hybrid systems and smart grids to support global energy security.